DEVELOPING STUDENT SOCIALIZATION THROUGH MOTOR ACTIVITIES - Ioan Sabin SOPA; Marcel POMOHACI (Editura Universităţii din Oradea, 2016)
: Starting from the assumption that motor activities are the perfect environment for socialization, communication and social integration of young people, this study aims to analyze the effectiveness of these activities in improving intergroup relations at the university level. In this research, the samples were composed of two groups, the experimental group (n = 25) with students from the Physical Education specialization and control group B (n = 25), composed of students from the Faculty of Sciences. The sociological survey applied on the two samples aimed to analyze the level of socialization, communication and social integration of students. The findings showed that the experimental group is more united, having a higher level of socialization and communication, compared to the control group B, proving once again the socializing effects of motor activities.